2015
DOI: 10.1515/math-2015-0071
|View full text |Cite
|
Sign up to set email alerts
|

Upper and lower bounds of integral operator defined by the fractional hypergeometric function

Abstract: Abstract:In this article, we impose some studies with applications for generalized integral operators for normalized holomorphic functions. By using the further extension of the extended Gauss hypergeometric functions, new subclasses of analytic functions containing extended Noor integral operator are introduced. Some characteristics of these functions are imposed, involving coefficient bounds and distortion theorems. Further, sufficient conditions for subordination and superordination are illustrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Motivated by the numerous allowances of the fractional derivative operators which have newly been reflected by many authors, here, we purposed two operators involving the generalized hypergeometric-type function and the generalized Beta function. Various studies can be found in [12,13,14].…”
Section: Resultsmentioning
confidence: 99%
“…Motivated by the numerous allowances of the fractional derivative operators which have newly been reflected by many authors, here, we purposed two operators involving the generalized hypergeometric-type function and the generalized Beta function. Various studies can be found in [12,13,14].…”
Section: Resultsmentioning
confidence: 99%
“…[2] In the twentieth century, the theory of Nonlinear functional integral equations has become an active area of research due to their applications in the fields such as engineering, mechanics, physics, chemistry, biology, economics and so on. For more details, one can see [3,4,5,6,7,8,9], and references therein.…”
Section: Introductionmentioning
confidence: 99%
“…Integral equations have a wide range applications in many fields of science, like physics, engineering economics and many other fields. (1,2,3,4,5) Various techniques have been devised by many researchers to solve the integral equations.…”
Section: Introductionmentioning
confidence: 99%